The implementation of the Water Framework Directive in Italy - Balzarolo D.; Lazzara P.; Colonna P.; Becciu G.; Rana G. (Dialogues on Mediterranean water challenges: Rational water use, water price versus value and lessons learned from the European Water Framework Directive, 2011)
This paper presents the main issues and trends in water resources management in Italy. After a description of water resources availability and use, as well as patterns of water management organization, the paper sketches the legislative history on national environmental issues and the administrative steps taken to transpone the European directive in Italian law. Furthermore, the actual implementation of WFD is discussed. In Italian legislation, water and environmental protection consisted of laws that gave incentives to water use to increase productivity. The aim of recent Italian legislation has been the development of land-use planning policies in correspondence with the physical and environmental characteristics of the land. The reference to these two aspects is one of the most innovative features of the new legislation, adopting a systemic approach to the problem of hydro-geological balance, at the same time protecting both land and water resources. Finally, we report on the case of the Po River District, which complies with the administrative and normative requirements of the European directives on environment and water. For this reason it represents a useful guidance for the rest of Italy, demonstrating how to implement the WFD and to develop effective, efficient and integrated water policy.
3. MELIA Workshop Water Value Impacts on the Mediterranean Water Policies, 2009/03/21-23, Istanbul (Turkey); 4. MELIA Workshop Benchmarking Exercise and Recommendations on the Application of the Water Framework Directive, 2010/03/21-26, Amman (Jordan)